The Mycotoxin Deoxynivalenol (DON) Promotes Campylobacter jejuni Multiplication in the Intestine of Broiler Chickens With Consequences on Bacterial Translocation and Gut Integrity - Ruhnau, Daniel; Hess, Claudia; Grenier, Bertrand; Doupovec, Barbara; Schatzmayr, Dian; Hess, Michael; Awad, Wageha A. (Frontiers in Veterinary Science, 2020)
Deoxynivalenol (DON) is one of the major health concern in poultry production as it targets epithelial cells of the gastrointestinal tract and contributes to the loss of the epithelial barrier function. It is well-documented that DON severely compromises various important intestinal functions in coincidence with aggravated clinical symptoms in livestock. In addition, a prolonged persistence of intestinal pathogens (e.g. Salmonella, Clostridium) in the gut has also been reported in pigs and chickens, respectively. Similar to DON, recent studies demonstrated that an experimental Campylobacter infection has severe consequences on gut health. Following oral infection, it was demonstrated that Campylobacter (C.) jejuni negatively affects the integrity of the intestine and promotes the translocation of bacteria from the gut to inner organs. So far, no data are available investigating the simultaneous exposure of DON and C. jejuni in broilers albeit both are widely distributed. Therefore, the aim of the present study was to investigate the interaction between DON and C. jejuni which is of a significant public and animal health concern as it may affect the prevalence and the ability to control this pathogen. Following oral infection of birds at 14 days of age with C. jejuni NCTC 12744, we show that the co-exposure to DON and C. jejuni has a substantial consequence on C. jejuni loads in chicken gut as well as on gut permeability of the birds. A reduced growth performance was found for DON and/or C. jejuni exposed birds. Furthermore, it was found that the co-exposure of DON and C. jejuni aggravated the negative effect on paracellular permeability of the intestine already noticed for the bacteria or the mycotoxin alone by the Ussing chamber technique. Furthermore, the increased paracellular permeability promoted the translocation of C. jejuni and E. coli to inner organs, namely liver and spleen. Interestingly, C. jejuni loads in the intestine were higher in DON-fed groups indicating a supportive growth effect of the mycotoxin. The actual study demonstrates that co-exposure of broiler chicken to DON and C. jejuni has not only substantial consequences on gut integrity but also on bacterial balance.